THE DISTRIBUTION AND SOME ECOLOGICAL ASPECTS OF MARINE ALGAL GENUS EUCHEUMA IN THE INDONESIAN WATERS - Atmadja, Wanda Surjana; Sulistijo, - (Marine Research in Indonesia, 1989)
Eight species of Eucheuma ait found to grow in the Indonesian waters making the amount of species of Eucheuma which had been found become 17 species. A certain species specifically found only in certain areas. Those species are usually found at the depths of 30 to 150 cm during low tide at the reef flat, moat and algal ridge of the coral reefs where temperatures and salinities varied from 29° to 31° and from 30 to 34? respectivelly. There are various habitats of Eucheuma i.e. dead and live corals, limestones, sand and shells. Average wet weight biomass of Eucheuma species at the areas investigated varied from 2 to 552 g/m . The highest value is that of Eucheuma spinosum found in East Seram (Maluku), and the lowest is that of E. cottonii found in the Keifing Island, East Seram. The species of Eucheuma commonly found in association with Acanthopora, Gracilaria and Halimeda. ABSTRAK